The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/cmar.s239593
|View full text |Cite
|
Sign up to set email alerts
|

<p>Increased Expression of TAP Is Predictive of Poor Prognosis in Patients with Non-Small Cell Lung Cancer</p>

Abstract: Background: The most common cancer among humans is lung cancer. Non-small cell lung cancer (NSCLC) comprises the majority of these cases. In the development and progression of cancers across the spectrum, tumor abnormal protein (TAP) plays crucial roles. Additionally, in the advancement of the bladder and colorectal cancers, the involvement of glycoproteins like TAP is present. However, it is worth noting that current literature has yet to clarify the clinical significance of the TAP in NSCLC. Methods: In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Many recent studies have demonstrated the sensitivity and specificity of TAP for the early screening, diagnosis, and prognosis of tumors. [8][9][10][11] In this study, we collected peripheral blood samples from 95 patients with gastric adenocarcinoma and 34 nontumor patients and evaluated the influence of TAP expression on screening diagnosis based on these samples. The positive rate of TAP in patients with gastric adenocarcinoma (68.4%) was significantly higher than that in nontumor patients (23.5%), indicating that TAP is more sensitive to gastric cancer; in other words, TAP can be used to monitor gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have demonstrated the sensitivity and specificity of TAP for the early screening, diagnosis, and prognosis of tumors. [8][9][10][11] In this study, we collected peripheral blood samples from 95 patients with gastric adenocarcinoma and 34 nontumor patients and evaluated the influence of TAP expression on screening diagnosis based on these samples. The positive rate of TAP in patients with gastric adenocarcinoma (68.4%) was significantly higher than that in nontumor patients (23.5%), indicating that TAP is more sensitive to gastric cancer; in other words, TAP can be used to monitor gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ESCC, TAP was also obviously expressed in stomach cancer, colorectal cancer, thyroid cancer, and bladder cancer, as well as lung cancer ( 9 12 , 21 , 22 ). The results of the study generally reviewed the role played by TAP in the development as well as the progression of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rates for patients with advanced and metastatic NSCLC are 24 and 4%, respectively [3]. Previous studies have reported a series of regulators involved in controlling NSCLC metastasis, including TWIST1 [4], PTCH1 [5] and TGF-β-induced long non-coding RNAs (lncRNAs) [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 5‐year survival rate of NSCLC remains low compared with other common cancers, such as colorectal, breast, and prostate cancers [ 2 ]. The 5‐year survival rates for patients with advanced and metastatic NSCLC are 24 and 4%, respectively [ 3 ]. Previous studies have reported a series of regulators involved in controlling NSCLC metastasis, including TWIST1 [ 4 ], PTCH1 [ 5 ], and TGF‐β‐induced long noncoding RNAs (lncRNAs) [ 6 ].…”
mentioning
confidence: 99%